Influence of Growing Medium on the Parameters and Yield Capacity of the Mini Tuber Potato of the Charoite Variety - A. Shelabina, Tamara; A. Danilov , Dmitriy; I. Rodionenkov, Aleksandr; A. Kuznetsov, Aleksey (KnE Life Sciences, 2021)
The creation of original seed grains of the Charoite variety, healed of pathogenic infections of various etiologies, was carried out through reproduction of the certified meristematic material of the microplants class. Mini tubers microplants were grown in 5.5 liter vessels on a “Agrobalt S” soil (control) mixed with peat and supplemented with 10% and 20% (of the volume) of the “ORVI” substrate. The use of the substrate “ORVI” mixed with peat and “Agrobalt S” soil positively influenced the growth, development and formation of tubers. The appliance of 10% of the “ORVI” substrate significantly increased the quantitative yield of mini tubers by 17% and the weight of tubers by 12.3%. The increase in the total number of mini tubers was due to the increase in tuber fraction from 10 to 30 mm. The appliance of a 20% “ORVI” substrate also led to an increase in the total number and mass of mini tubers. According to the EIA results, the mini tubers grown from microplants did not contain any latent viral infection. Tests on the seeds did not reveal symptoms of fungal diseases. Keywords: breed, potatoes, mini tubers, mass of tubers, peat fertilizer, substrate